El valor de los Incoterms para precisar el juez del lugar de entrega - Castellanos Ruiz, Esperanza (CUADERNOS DE DERECHO TRANSNACIONAL, 2012)
The art. 5.1.b) of Council Regulation (EC) Nº 44/2001 of 22 December 2000 on jurisdiction and the recognition and enforcement of judgments in civil and commercial matters states that have jurisdiction to hear in disputes arising from a contract of the sales of goods the courts of «the place of delivery», «under the contract», as «the place of performance of the obligation in question». Incoterms provide and fix clearly the place of delivery of goods depending on Incoterms used, so the STJUE of 9 June 2011, in the case Eurosteel Europe, have been used to determine the competent court. The most serious problem arises when the parties do not compromise the delivery location. In this case, we study the various possible solutions to determine the place of delivery: Incoterms, United Nations Convention on the International Sale of Goods of April 1980, Rome I Regulation..., and possible legal consequences. Not forgetting that Incoterms also have been used as Lex contractus.
Keywords: art. 5.1.b) of Council Regulation 44/2001; art. 31 CISG; international sale of goods; place of delivery under the contract; Incoterms; the final destination of the sales transaction; transfer of risks